Weak solutions of coupled variable-density flows and heat transfer in porous media. (August 2022) - Beneš, Michal
Abstract: We consider a fully nonlinear degenerate parabolic system describing the three-dimensional variable-density Darcian flow of a heat conducting fluid through porous media. We establish the global existence of weak solutions to the relevant initial-boundary value problems in nonsmooth domains under physically reasonable hypotheses on the data and mixed boundary conditions.